Dietary inulin modulated the cortisol response and increased the protection against pathogens in juvenile pacu (Piaractus mesopotamicus) - de Campos, Cristiane Meldau [UNESP]; Zanuzzo, Fabio Sabaddin [UNESP]; Gimbo, Rodrigo Yukihiro [UNESP]; Favero, Gisele Cristina [UNESP]; Soares, Michelly Pereira; Pilarski, Fabiana [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Hindawi, 2021)
Inulin is a prebiotic that plays an important role in improving health and immunity in humans, animals and fish. We tested whether inulin supplementation would improve the immune protection of juvenile pacu (Piaractus mesopotamicus) exposed to capture and transfer of tanks followed by bacterial inoculation. For this, we fed fish for 15 days with diets supplemented with 0.5% or 1.0% of inulin and evaluated the levels of plasma cortisol, glucose and chloride; the leucocyte respiratory activity (RAL); the serum levels of lysozyme; haematological parameters and the profile of circulating leucocytes before and 1 h after the management and at 3, 6 and 24 h after inoculation of Aeromonas hydrophila. The stress caused by the management and inoculation was confirmed by increased glucose and cortisol concentrations 1 h after the procedure and 6 and 24 h after inoculation respectively. Inoculation reduced RAL earlier (3 h) and increased lysozyme later (24 h). Thrombocytes and leucocytes decreased after inoculation, and lymphocytes decreased after capture and transfer of tanks and inoculation, while neutrophils increased after both procedures. The inulin supplementation reduced the cortisol response, increasing the chloride levels before and after the stressor. Inulin increased the serum lysozyme concentration but did not modulate RAL and leucocyte responses in blood. The inulin supplementation for 15 days minimized the stress response and increased the innate immune responses in pacu; therefore, this feed additive can help improve the health of farmed fish.
Keywords: bacterial challenge; fructooligosaccharide; Piaractus mesopotamicus; prebiotic